Ten-Year Interval Changes in the Prevalence of Self-Identified Premature Ejaculation and Premature Ejaculation Based on an Estimated Intravaginal Ejaculation Latency Time of <3 Minutes in the General Population: The Korean Internet Sexuality Survey (KISS) 2016. Issue 4 (1st April 2019) - Song, Won Hoon; Yoo, Sangjun; Oh, Sohee; Park, Juhyun; Cho, Sung Yong; Cho, Min Chul; Jeong, Hyeon; Son, Hwancheol
ABSTRACT: Introduction: Because the prevalence of premature ejaculation (PE) may change with time, few studies have been conducted over a 10-year time interval. Aim: A 10-year time interval survey to determine whether there was a change in the prevalence of self-identified PE and PE defined on the basis of an estimated intravaginal ejaculation latency time of <3 minutes in adult Korean men, even after adjusting for various sociocultural factors. Methods: We sent an e-mail to the panels registered in the same Internet survey agency in 2006, asking them to participate in a questionnaire-based survey of the same study design. 1, 401 participants were enrolled in the 2016 study that included 800 subjects in their 20s–50s. The PE prevalence adjusted for age was evaluated because the proportion of participants per age was different between the 2 surveys. The age-adjusted prevalence of self-identified PE and PE with an estimated intravaginal ejaculation latency time of 3 minutes, which meets the diagnostic criteria for PE set by the International Society for Sexual Medicine ( PE ), was evaluated. Main Outcome Measures: Changes in the overall prevalence of self-identified PE and PE in over a decade were evaluated. Results: The overall age-adjusted prevalence of self-identified PE increased from 19.0% in 2006 to 21.6% in 2016; however, the result was not statistically significant ( P  = .244). The overall age-adjusted prevalence of PE increased from 1.8–4.0% in 2006 and 2016, respectively ( P  = .012). The risk factors of self-identified PE were few intercourses per month, masturbation, and self-identified erectile dysfunction. In addition, the risk factors of PE were aging, high body mass index, few intercourses per month, and masturbation. Clinical Implication: The prevalence of PE has increased over 10 years. However, this increase may be due to sociocultural changes and should be more concerned with these factors. Strength & Limitations: This study was the first to conduct a 10-year interval Web-based survey on the prevalence and risk factors of PE. However, this was not a cohort study with the same participants. Conclusion: The overall age-adjusted prevalence of PE increased significantly over a decade, and sociocultural factors such as lifestyle were associated with the difference of PE prevalence for 10 years. However, more research is needed to determine how these sociocultural changes affect PE prevalence.